GUIDANCES FOR TEENAGERS: ETHOS, SCENOGRAPHY AND STEREOTYPES - Brunelli, Anna Flora [UNESP]; Fossey, Marcela Franco; Furlan, Marilia Molina [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2018)
In this paper, based on the thoughts that Dominique Maingueneau develops on the enunciative aspects of discourse, we analyze the orientation discourse for teenagers, trying to apprehend the image of teenagers that the discourse projects. More precisely, considering certain enunciative mechanisms that characterize this discourse, we analyze the ethos of the enunciator and the scenography in which it emerges. The analysis reveals that the guarantor, inserted in scenarios of an informal conversation, is related to a juvenile ethos. Moreover, the analysis reveals that in this discourse the image of the enunciator, considered essentially as an insecure and immature young person, prevails over that of the enunciator.
Keywords: guidances; teenagers; ethos